Model Hibrid Tri Pramana dan Bloom's Digital Taxonomy Untuk LMS Pendidikan Agama Hindu Berorientasi HOTS - I Wayan Wira Darma; L. Eka M. Julianingsih P.; Gede Agus Jaya Negara (Jayapangus Press, 2026)
The development of Learning Management Systems (LMS) oriented toward Higher-Order Thinking Skills (HOTS) that integrate local Hindu wisdom remains highly limited, and the digitalization of Hindu religious education in higher education has yet to be supported by a pedagogical framework that synthesizes Hindu epistemology with contemporary learning taxonomies. This study aims to develop, validate, examine the practicality of, and measure the effectiveness of a hybrid pedagogical model that synthesizes Tri Pramana epistemology with Bloom's Digital Taxonomy as the framework of an LMS for Hindu religious education. A Design and Development method employing the ADDIE framework was applied, involving two content experts, two media experts, eight lecturers, and 86 students from the Hindu Religious Education Study Program at IAHN Mpu Kuturan. Data were collected through validation questionnaires, response questionnaires, and HOTS achievement tests, then analyzed using mean scores, percentages, and N-gain. Expert validation indicated that the model was highly valid, with a mean score of 4.50, while the practicality test yielded positive responses from lecturers (91.20%) and students (88.75%), categorized as highly practical. The effectiveness test revealed an increase in mean scores from 52.35 (pretest) to 86.67 (posttest), and classical learning mastery rose from 34.88% to 91.86%. The overall N-gain reached 0.72 (high), with a graduated pattern of C6 Creating (0.80), C5 Evaluating (0.72), and C4 Analyzing (0.64), demonstrating that the greatest improvement aligned with the Anumana Pramana phase. The five-stage reasoning structure of Anumana Pramana, supported by e-portfolio, digital debate forums, and collaborative evaluation rubrics, most effectively cultivated HOTS.